2022
DOI: 10.1086/720630
|View full text |Cite
|
Sign up to set email alerts
|

The Comparative Advantage of Firms

Abstract: Resource based theories propose that firms grow by diversifying into products which use common capabilities. We provide evidence for common input capabilities using a policy that removed entry barriers in input markets to show that the similarity of a firm's and industry's input mix determine firm production choices. We model industry choice and economies of scope from input capabilities. Estimating the model for Indian manufacturing, input complementarities make firms 5% more likely to produce in an industry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 97 publications
(99 reference statements)
0
14
0
Order By: Relevance
“…Recent literature on multi-product firms hints at the source of relatedness in technologies. According toBoehm et al (2022), input capabilities determine the evolution of multi-product firms' product spaces. By analyzing India's manufacturing data, they showed that input capabilities affected firms' core competencies, and in turn, core competencies determined product diversification in multi-product firms.…”
mentioning
confidence: 99%
“…Recent literature on multi-product firms hints at the source of relatedness in technologies. According toBoehm et al (2022), input capabilities determine the evolution of multi-product firms' product spaces. By analyzing India's manufacturing data, they showed that input capabilities affected firms' core competencies, and in turn, core competencies determined product diversification in multi-product firms.…”
mentioning
confidence: 99%
“…a change in regulation specific to small and medium size firms). Data on dereservation events come from Boehm, Dhingra, and Morrow (2019). In even columns, we include the whole sample but interact I High M RP K i with an indicator variable Dereservation jt that is equal to 1 after the industry has been dereserved.…”
Section: Discussionmentioning
confidence: 99%
“… To develop our dereservation measure, we use the list of deregulated industries in ASICC from Boehm, Dhingra, and Morrow (2022) and create a crosswalk between ASICC and our definition of industry (NIC 2008) by using the ASI 2008–2009. For each establishment in the ASI, the data report both the NIC code of the establishment and the list of all the products sold at the ASICC level.…”
mentioning
confidence: 99%
“…Our focus on firms' decision to produce knowledge in-house is closest to Teece (1982), who posits that multi-product firms can be rationalized by "organizational knowledge," and Demsetz (1988) who argues that "knowledge is costly to produce, maintain, and use" (p. 157). More recently, Boehm et al (2022) show that common input knowledge facilitates expansion into new products, Atalay et al (2014) argue that the transfer of intangibles across plants is an important motive for integration, Ding (2020) provides evidence that knowledge inputs are shared within multi-industry firms, and Mengus and Michalski (2022) report that certain service workers augment in-house knowledge. Our contribution is to expand the analysis to non-manufacturing, construct a new measure of firms' in-house knowledge, and show that firms with this in-house knowledge both grow and pivot more in response to shocks.…”
Section: Introductionmentioning
confidence: 99%